(3OhQ GdHfhc GdJLGQjI aj GSJKeGQ GehGd GdYedGA (B/s - (3GdfUQ, SYjO Sjas ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2004)
(3aj gPG GdcJGH (B: (3hXjaI GdHfc GdJbdjOjI aj GSJKeGQ CehGd GdYedGA hSGFd GdHfhc aj JLejY hOGFY GdYedGA ; SjGSI GdHfhc aj GSJKeGQ fbhO GdhOGFY GdOhQ GdLOjO ddHfhc GdJLGQjI cCefGA GSJKeGQ GOGQI GehGd GdYedGA hGdNOeGJ GdGNQi GdeQJHWI HgG ;GOGQI eMGaX GdGhQGb GdeGdjI OhQ GdHfc ceSJKeQ dCehGd GdYedGA ef GdhLgI GdbGfhfjI GdWHjYI GdbGfhfjI dOhQ dOhQ GdHfc ceSJKeQ dCehGd GdYedGA, eOi eDhdjI GdHfc JLGg GdYedGAs
(3HjHdjhZQGajG U(B. 426s
Keywords: (3GdGSJKeGQ GdeUQajs; (3GdGhQGb GdJLGQjIs; (3GdHfhc GdJLGQjIs